A Concept of Housing and Settlements based Sustainable Spatial Articulation for Indonesian Cities (International Journal of Scientific Research and Management (IJSRM), 2022)
This article aimed at introduce and offer a concept of ’spatial articulation’ that sustainable in developing the ideal urban housings and settlements in Indonesia, ’Spatial Articulation’ is a concept or a theory developed from the theory of ’Articulation of Mode of Production’—A theory in the realm of macro sociology that offers the assumption that social formations on the periphery (developing countries) are mastered, at least, by two modes of production, capitalist mode of production and pre-capitalist mode of production—where one of them dominated the other(s). In addition, Urban Critical theories and Henri Lefebrve’s concept on Production of ​​Space also contributed to the birth of the Theory of Urban Spatial Articulation. The assumption is that when the capitalists sector reproduces the "abstract (that planned) spaces”, then sooner or later, the pre-capitalist sector will do the articulation by reproducing the "differential (that unplanned) space” in or around the "abstract spaces" that reproduced by the capitalist sector.